Ultrasound and histopathological assessment of benign, borderline, and malignant thyroid tumors in pediatric patients: an illustrative review and literature overview - Dominika Januś; Dominika Januś; Monika Kujdowicz; Monika Kujdowicz; Aleksandra Kiszka-Wiłkojć; Aleksandra Kiszka-Wiłkojć; Konrad Kaleta; Anna Taczanowska-Niemczuk; Anna Taczanowska-Niemczuk; Jan Radliński; Kamil Możdżeń; Zuzanna Nowak; et al. (Frontiers in Endocrinology)
BackgroundThe risk of malignancy in thyroid nodules is higher in children than in adults, often necessitating a more aggressive endocrine and surgical approach. However, given that not all solid thyroid nodules are malignant, a more conservative approach may also be appropriate in certain cases.ObjectiveThis study aims to present an illustrative analysis of the pathological foundations underlying the sonographic appearance of benign, borderline, and malignant thyroid nodules in the pediatric population at a single tertiary thyroid center.MethodsA total of 47 well-documented pediatric patients referred for thyroid surgery between 2010 and 2023 were analyzed. This retrospective assessment included an examination of demographic data, hormonal profiles, ultrasound findings, and histopathology reports.ResultsUltrasound and histopathology of thyroid nodules provided insights into subgroup differentiation. Benign nodules like dyshormonogenetic goiter showed solid hypoechoic features on ultrasound and dense fibrosis on histopathology, while thyroid follicular nodular disease exhibited isoechoic nodules with halos, histologically revealing dilated follicles. In borderline tumors, well-differentiated tumor of uncertain malignant potential (WDT-UMP) nodules were hypo/hyperechoic with occasional capsular invasion, resembling papillary thyroid carcinoma (PTC) features histologically. Non-invasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) appeared as well-defined hypoechoic nodules with a hypoechoic rim, with histology showing follicular architecture and PTC nuclear features, but no invasion. Follicular tumor of uncertain malignant potential (FT-UMP) displayed hypo/hyperechoic patterns and indistinct borders, with uncertain capsular invasion and no PTC nuclear features. Malignant lesions showed distinct patterns: PTC as hypoechoic, irregular nodules with mixed vascularization, follicular thyroid carcinoma as large, hyperechoic nodules with invasive features, and poorly differentiated thyroid carcinoma (PDTC) as heterogeneous hypoechoic masses.ConclusionBecause of the significant overlap in sonographic features among benign, borderline, and certain malignant thyroid lesions in pediatric patients, ultrasonography alone is insufficient for accurate risk stratification. This overlap necessitates referrals for fine-needle aspiration biopsy (FNAB) in children more frequently than in adults. Future studies utilizing artificial intelligence (AI) to predict clinical outcomes in thyroid nodule diagnostics may offer new advancements, particularly given the increasing number of pediatric patients with solid thyroid lesions.